Brand knowledge of Lexus According to the Younger Segment Group - Siahaan, Nadissa; Indriani, Mia Tantri Tantri Diah (Journal of Business and Management, 2015)
Abstract - Lexus is the luxury vehicle brand, owned by Toyota Motor Corporation, which values the products and experiences that offer luxury, comfort, and innovation. Lexus was introduced in Indonesia 2007, and now they plan to expand their market segment by launching their new product for younger age, soon. Since they are considered as a new brand on the luxury car market, it has to compete with those well-known European luxury brands. It is a tight competition, because the competitors have already had strong brand image that had been built years before. So this research was aimed to find out younger generation’s perception towards Lexus, through the brand awareness and brand image. Those findings are collected by a qualitative research through the free association method and picture response technique, which are conducted by the younger generation as the respondents. This research revealed that the brand image of Lexus is well captured by younger generation, because most of respondents have positive images toward Lexus, and already have some knowledge about Lexus. Younger age tends to be lifestyle oriented and aspired to high-end people, and Lexus is considered to be a tool to gain prestige and social recognition. But the awareness of Lexus is still attached with Toyota, which leads to negative association towards the brand itself. Moreover, younger age perceives the luxurious only on the product’s image, whereas Lexus also offers the luxury value through the experiences. By the result of this research, Lexus is suggested to conduct a marketing strategy to loosen the attachment between Toyota and Lexus. Lexus also needs to make an effort in certain direction to strengthen its value, which is the luxury experience, to the younger age. So, the opportunity to approach this new-targeted sub-segment will be more widely open.Keywords: Brand, Brand Image, Brand Awareness, Brand Knowledge, Lexus, Younger Generation, Younger Age.